1983
DOI: 10.1042/cs0640231
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Infused [14C]Bicarbonate as Respiratory 14CO2 in Man

Abstract: 1. Nine adult subjects (eight obese, one normal) were infused with NaH14CO3 for up to 36 h. 2. The recovery of label as respiratory 14CO2 was close to 90% throughout and did not change with feeding or with dietary composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Others have reported on the coefficient of variation of 'plateau' recovery, which takes into account C02 production, e.g. 1-3% [23] or 6% [9]. One study has reported on the coefficient of variation ( < 10%) associated with the measurement of C02 production [2], but many studies do not give such results (e.g.…”
Section: Period Of Infusionmentioning
confidence: 94%
See 2 more Smart Citations
“…Others have reported on the coefficient of variation of 'plateau' recovery, which takes into account C02 production, e.g. 1-3% [23] or 6% [9]. One study has reported on the coefficient of variation ( < 10%) associated with the measurement of C02 production [2], but many studies do not give such results (e.g.…”
Section: Period Of Infusionmentioning
confidence: 94%
“…No relationship was found between the priming dose and recovery of label, but the use of different protocols, which involved assessment of recovery over widely different periods of time, and the use of different methods to analyse the results, confounds interpretation. [8,9,11,12,15,16,25,29,30,321 and five of these whole-body calorimetry [9,11,12,15,251. Eight studies used a hood or a face mask to measure the COz production intermittently.…”
Section: Period Of Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the error introduced by retention of labelled CO2 has been re-examined (Clugston & Garlick, 1983;Irving, Wong, Wong, Boutton, Shulman, Lifschitz, Malphus, Helge & Klein, 1983). To avoid uncertainty some workers now routinely give a primed infusion of labelled bicarbonate before the amino acid infusion (Matthews et al 1980;Clague, Keir, Wright & Johnston, 1983).…”
Section: Methods Of Measuring Protein Turnover In the Living Animalmentioning
confidence: 99%
“…We calculated the instantaneous rate of label oxidation (T; [32] for substrate labelled with a single 13 C per molecule. We used a bicarbonate retention factor of 86 per cent because previous studies in various mammal taxa consistently showed that bicarbonate retention was almost identical across taxa [38][39][40][41]. Any deviation between assumed and true bicarbonate retention factors may not affect the relative difference in our estimates of compound-specific oxidation rates because this constant applies to both calculations in the same way.…”
mentioning
confidence: 99%